Fenomen preodoleniya v psikhologicheskoi podgotovke sportsmenov - Andreeva, V. V. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The traditional position about the overcoming of difficulties is described as well as the characteristic of the phenomenon of overcoming. Some examples from the psychotherapeutic practise are presented as well as some tipps for psychological training.